Alterações no equilíbrio ácido-base em equinos submetidos à prova de três tambores ou à competição de enduro de 160 Km - Brito, Helena Cristina Delgado [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of the present study was to determine physiological, electrolytic and hemogasometric parameters of Quarter horses, with distinct fitness levels, submitted to a simulated barrel racing (BR). Moreover, the alterations in the acid-base balance were compared between Quarter and Arabian horses, competitors of equine endurance of 160 km. Besides, it was performed a comparison of two methods to determine the variable Atot. In the experiment 1, 10 Quarter horses were distributed in two groups, one composed by high fitness animals (HF, n=5) and other with lower fitness (LF, n=5). These horses were submitted to a BR and it was verified the possible alterations in the acid-base balance using the traditional and mechanistic approaches, being the collecting moments before and after the exercise. In the experiment 2, 16 Arabian horses participated in an endurance ride of 160 km and they were evaluated before, during and after the competition. Samples of venous blood were collected in both experiments. The heart frequency was determined only for the Quarter horses. Physiological, electrolytic and hemogasometric parameters were quantified for all equines of the present study. Were performed for the experiment 1, the t-paired and not-paired t-test between moments and groups, respectively. For the experiment 2, it was performed the analysis of variance (ANOVA) to compare the variables followed by Tukey’s test. All analysis were performed with 95% of significance. The FCpeak e FCm were 206 ± 8,7 and 203 ± 12,9 bpm for the HF group, and 181 ± 7,5 e 177 ± 3,5 bpm for the LF group. The main disturbance found by the two approaches for the BR was the metabolic acidosis. For this discipline, total matching between the approaches was obtained. For endurance, 10 animals sucessfully completed the competition and 6 were eliminated. The main disturbance found in the sucessfull animals for both approaches was the metabolic alkalosis. In the ...

Objetivou-se determinar variáveis fisiológicas, eletrolíticas e hemogasométricas de equinos da raça Quarto de Milha (QM), com desempenhos distintos, submetidos a uma corrida simulada de três tambores (TT). Ademais, compararam-se as alterações no equilíbrio ácido-base destes equinos QM com outros atletas da espécie equina, da raça Puro Sangue Árabe (PSA), competidores de enduro equestre de 160 km de distância. Adicionalmente, realizamos a comparação de dois métodos de cálculo da variável Atot. No experimento 1, 10 equinos da raça QM foram distribuídos em dois grupos, sendo um de desempenho superior (DS, n=5) e outro de desempenho inferior (DI, n=5). Submeteram-se estes equinos a uma corrida de TT e verificou-se as possíveis alterações no equilíbrio ácido-base pela abordagem tradicional e mecanicista, sendo os momentos de coleta antes e após o esforço. No experimento 2, 16 equinos da raça PSA participaram de uma prova seletiva de enduro equestre de 160 km e foram avaliados antes, durante e após a competição. Amostras de sangue venoso foram coletadas em ambos os experimentos. Determinou-se frequência cardíaca somente dos equinos QM. Quantificou-se variáveis fisiológicas, eletrolíticas e hemogasométricas de todos os equinos que participaram do presente estudo. Realizou-se para o experimento 1, teste t pareado e não pareado para diferenças entre os momentos e entre os grupos, respectivamente. Para o experimento 2, foi realizada análise de variância (ANAVA) para comparação das variáveis seguido do teste de Tukey para as diferenças estatísticas encontradas. Todas as análises foram realizadas com 95% de significância (p<0,05). As FCpico e FCm foram de 206 ± 8,7 e 203 ± 12,9, e de 181 ± 7,5 e 177 ± 3,5 bpm, para os grupos DS e DI, respectivamente. O principal distúrbio encontrado pelas duas metodologias para a modalidade TT foi a acidose metabólica. Para esta modalidade obtivemos concordância total...
Keywords: Equino; Cavalo de enduro; Equilibrio acido-base; Físico-química; Fisiologia veterinaria; Endurance horses